UPAYA MENINGKATKAN MINAT MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) - Ika Septi Hidayati (Academy of Education Journal, 2017)
The purpose of this study are (1) To find out the application of the right type of team assisted Individualization (TAI) cooperative learning model in order to increase the interest in learning of third grade students of Prembulan Galur Kulon Progo State Elementary School. (2) Knowing the strengths and weaknesses of the team assisted Individualization (TAI) type of cooperative learning model in increasing the interest in learning for students in grade III at Prembulan Galur Kulon Progo State Elementary School. (3) Determine the effectiveness of the team assisted Individualization (TAI) type of cooperative learning model in increasing the interest in learning of third grade students of Prembulan Galur Kulon Progo State Elementary School. The results of this study indicate that: (1) In general, the application of an appropriate TAI learning model, effective in increasing interest in learning mathematics, (2) Increasing students' interest in learning mathematics towards Elementary School Prembulan III in pre-cycle of 64 in cycle I amounted to 76.04 in second cycle of 85.93.